Glycosylation of recombinant adeno-associated virus serotype 6 - Yuki Yamaguchi; Kentaro Ishii; Sachiko Koizumi; Hiroaki Sakaue; Takahiro Maruno; Mitsuko Fukuhara; Risa Shibuya; Yasuo Tsunaka; Aoba Matsushita; Karin Bandoh; Tetsuo Torisu; Chie Murata-Kishimoto; et al. (Molecular Therapy: Methods & Clinical Development, 2024)
Glycosylation of biopharmaceuticals can affect their safety and efficacy. Glycans can occur on recombinant adeno-associated viruses (rAAVs) that are used for gene therapy; however, the types of glycans that attach to rAAVs are controversial. Here, we conducted lectin microarray analyses on six rAAV serotype 6 (rAAV6) preparations that were produced differently. We demonstrate that O-glycans considered to be attached to rAAV6 were recognized by Agaricus bisporus agglutinin (ABA) and that N-glycans were detected in rAAV6 purified without affinity chromatography. Liquid chromatography-tandem mass spectrometry (LC-MS/MS) analysis showed that the N-glycans detected in rAAV6 were derived from host cell proteins. A combination of ABA-based fractionation and LC-MS/MS revealed that rAAV6 was O-glycosylated with the mucin-type glycans, O-GalNAc (Tn antigen), and mono- and di-sialylated Galβ1-3GalNAc (T antigen) at S156, T162, T194, and T201 in viral protein (VP) 2 and with O-GlcNAc at T242 in VP3. The mucin-type O-glycosylated rAAV6 particles were 0.1%–1% of total particles. Further physicochemical and biological analyses revealed that mucin-type O-glycosylated rAAV6 had a lower ratio of VP1 to VP2/VP3, resulting in a lower transduction efficiency both in vitro and in vivo compared with rAAV6 without mucin-type O-glycans. This report details conclusive evidence of rAAV glycosylation and its impact on rAAV-based therapeutics.